Mycoflora and Natural Incidence of Selected Mycotoxins in Rabbit and Chinchilla Feeds - Greco, Mariana Vanesa (The Scientific World Journal, 2012)
Mycotoxins are secondary metabolites produced by filamentous fungi that cause a toxic response when ingested by animals or man. Demand of natural fur, such as those from rabbit and chinchilla, produced under controlled conditions, has increased worldwide. The toxicogenic mycoflora contaminating feeds for these animals was enumerated and identified. Six of the major mycotoxins implicated in animal mycotoxicosis were detected and quantified. Moulds count ranged from <10 to 4.7 × 10(5) CFU g(−1); 14% of the samples exceeded the limit that determines hygienic feed quality. More than twenty species belonging to the five most important mycotoxigenic mould genera were recovered. Among the analyzed mycotoxins, aflatoxins were recovered in 100% of the examined samples, deoxynivalenol in 95%, fumonisins in 100%, ochratoxin A in 98%, T2 toxin in 98%, and zearalenone in 100%. Cooccurrence of mycotoxins was observed in 100% of the samples analyzed. Exposure to multiple mycotoxins was thus demonstrated for these animals.